Green Education in Post-Conflict Settings: A Systematic Review of Its Prospects, Challenges, and Implementation Requirements in Libya (Al-Farooq Journal of Sciences, 2026)
This research aims to analyze the concept of green education and explore its potential, obstacles, and requirements for implementation in post-conflict contexts, with a focus on the Libyan case as a model of a country facing intertwined transitional and developmental challenges. To achieve the objectives of the study, the descriptive analytical approach was adopted, based on a systematic review of the scientific literature guided by the PRISMA criteria. Comparative analysis was also employed to benefit from relevant international experiences and examine the possibility of applying them within the Libyan context.The review included more than 60 peer-reviewed studies published between 2015 and 2025 in Scopus, Web of Science, and Semantic Scholar databases, in addition to international reports issued by organizations concerned with development, education, and sustainability.The findings revealed that green education represents one of the important approaches to supporting sustainable development, enhancing environmental awareness, and building competencies capable of addressing the challenges of climate change and the green economy, particularly in fragile and post-conflict environments. The results also showed that Libya possesses several supportive factors for the implementation of green education, most notably natural potential related to renewable energy, a young demographic structure, and educational institutions that can be developed. However, these opportunities are accompanied by a set of challenges related to weak specialized educational policies, limited funding, institutional and digital fragility, and the insufficient integration of sustainability concepts into curricula and public discourse.The research concluded with a set of recommendations to support the adoption of green education in Libya. These recommendations include developing relevant policies and legislation, strengthening teacher preparation, updating curricula, expanding institutional partnerships, and supporting educational initiatives related to sustainability.
Keywords: Green education; sustainable development; education for sustainability; post-conflict contexts; Libya; fragile contexts; green competencies